Development of small medium enterprises of maize processed food products as a locomotive of Gorontalo District’s economy - Amir Halid (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
This study aims to analyze the development of small medium enterprises (SMEs) of maize processed product as a locomotive of Gorontalo District’s economy. Primary and secondary data were used for this study. Data were analyzed descriptively and regression analysis was conducted to analyze the effect of the components of production costs on the selling prices of maize processed food products and the effect of selling prices on SMEs revenues. The results of the study found that the potential for development of SMEs of maize processed food products in Gorontalo District is quite prospective because human resources and raw materials were still cheap and easily obtained. On the demand side, maize processed products are also relatively high on demand. Maize processed product has been an alternative substitute for pastries which are always served by Muslims on religious observances. In increasing the competitiveness of maize processed products, it is necessary to pay attention and make raw material costs and labor costs efficient. Those two cost components have a significant effect on the selling prices of maize processed food products.